Antimicrobial resistance and virulence of carbapenem-resistant Klebsiella pneumoniae strains isolated from children in intensive care and surgical units - Irina E. Novikova; Zulfirya Z. Sadeeva; Natalya M. Alyabyeva; Ekaterina A. Samoylova; Olga V. Karaseva; Olga G. Yanyushkina; Anna V. Lazareva (Журнал микробиологии, эпидемиологии и иммунобиологии, 2023)
Introduction. Infections associated with carbapenem-resistant (Carba-R) Klebsiella pneumoniae (KP) are a serious public health problem because they lead to an increase in hospital stays, treatment costs, and an increase in patient morbidity and mortality.